2019
DOI: 10.1371/journal.pone.0212753
|View full text |Cite
|
Sign up to set email alerts
|

Predicting resource-dependent maternal health outcomes at a referral hospital in Zanzibar using patient trajectories and mathematical modeling

Abstract: Poor intra-facility maternity care is a major contributor to maternal mortality in low- and middle-income countries. Close to 830 women die each day due to preventable maternal complications, partly due to the increasing number of women giving birth in health facilities that are not adequately resourced to manage growing patient populations. Barriers to adequate care during the ‘last mile’ of healthcare delivery are attributable to deficiencies at multiple levels: education, staff, medication, facilities, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Midwives are the obstetrician's right hand to carry out initial treatment for maternal referrals according to instructions because obstetricians do not stand by 24 h at the referral hospital, while pregnant women who get referrals need urgent action to prevent delays inadequate service. Nadkarni et al explained that in their research, doctors did not stay by every shift, increasing the number of maternal mortality by tenfold [49]. This is consistent with Ghana's research because the delay in intervention by obstetricians to pregnant women at referral hospitals is one of the main factors in maternal mortality [50], [51].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Midwives are the obstetrician's right hand to carry out initial treatment for maternal referrals according to instructions because obstetricians do not stand by 24 h at the referral hospital, while pregnant women who get referrals need urgent action to prevent delays inadequate service. Nadkarni et al explained that in their research, doctors did not stay by every shift, increasing the number of maternal mortality by tenfold [49]. This is consistent with Ghana's research because the delay in intervention by obstetricians to pregnant women at referral hospitals is one of the main factors in maternal mortality [50], [51].…”
Section: Discussionmentioning
confidence: 52%
“…Sharan et al mentioned that in CEmOC and non-CEmOC referral hospitals in Eritrea, most obstetricians take the optimal day and night shifts to provide direct referral care to pregnant women to minimize morbidity and mortality [54]. Other studies describe secondary facilities as referral places that must have complete staff in pregnant women at risk, resulting in overall maternal health [49]. The importance of a 24-h stand-by obstetrician in referral services at the hospital to provide care and direct case management for pregnant women at risk is proven to provide adequate care, resulting in maternal and infant health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported predictive models formed from ML methods, and one study was a report of NLP used to transform clinical notes into assessment forecasting. The Nadkarni 165 research group used a stepwise, iterative, object-oriented program written with workflow and treatment processes in mind in a sample of 343 patients with potentially life-threatening complications and 2,285 uncomplicated mothers in a Tanzanian hospital. Aimed at providing decision makers with a tool to analyze the impact of resource limitations on maternal inpatient complications, key variables included treatment efficacy, severity distribution, number and frequency of nurse visits, nurse staffing at the shift level, deterioration rate, and maternal near-misses.…”
Section: Staffing/scheduling/workloadmentioning
confidence: 99%
“…Two studies 29,162 reported predictive models formed from ML methods, and one study 163 was a report of NLP used to transform clinical notes into assessment forecasting. Each had retrospective designs using secondary data, two used a single tertiary care setting 29,162 (tertiary care, maternal care), and one 163 used two matched psychiatric settings. Diverse samples were used, with one study 162 using over 2500 maternal inpatients, another 29 using over 800 medical/surgical inpatients, and the remaining study 163 sampling the admission encounters of over 5000 psychiatric patients.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation